A Colonial Factory of Property Rights: Contribution to an Archeology of Naturalism - Bertrand, Aliènor (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2018)
This article presents a new genealogy of modern property rights that cannot be overridden either by the narrative that links the exclusive right of use to the progression of individual freedoms, or by the narrative that makes it a European construction formalizing the capitalist appropriation of the means of production, particularly during the movement of enclosures. It explores the history of the first colonization and the extraordinary effort of legal elaboration that accompanied it. The Iberian conquest was a time of a break in the medieval rights regime. In Spanish America, for the first time, the law no longer had the function of regulating uses, powers and exchanges in a system of entangled obligations and prerogatives linked to the land: in forms borrowed from medieval law, it instituted a radically new social order linked to the extreme violence of the first decades of the conquest. The history of this institution testifies to the strong tensions between the extortion practices imposed on conquered territories and peoples and the ancient representation of the destination of the right, particularly the right of persons linked to the status of subject of the Spanish Crown. Among the medieval legal forms that found a new destination, the encomienda was one of the first and one of the most important. But if it can legitimately be considered as one of the roots of modern property law, it is not as an archaic prototype of exclusive ownership, since it is not itself a land right. It was above all a right of command over the colonized persons, or, more precisely, a double right: a right of powerful destruction of existing uses legitimized by Christianization, and a right of coercion to productive work. Encomienda thus dislodges in its principle the medieval legal entanglement interweaving the status of people and land, and institutes the social relations that conditioned the emergence of the capitalist principle of ownership of the means of production as exclusive property.